THE OVERVIEW ON THE WORKS PUBLISHED BY MUNSHI NAVAL KISHORE’S PUBLISHING HOUSE IN THE NATIONAL LIBRARY IN ALMATY - С. Жусуповa (Journal of Oriental Studies, 2019)
In the article I am going to make the review on the works published by Munshi Naval Kishore’s publish- ing house in Persian who was a popular publisher, writer and printer founded the popular publishing house named ‘Newal Kishore Press and Book Depot’ in Laknow, India. Thanks to them, more than 5,000 works in Urdu, Hindi, the Arab and Persian languages have been published. The purpose of this research consists of making the analysis of the publications printed under Munshi Naval Kishore’s management, which have reached the territory of Kazakhstan since the 19th and remained in National library of Almaty by today. Namely, I would like to investigate the present condition of these books, how they have remained up to this moment, how their pages, covers, font and registration do look. Besides, I want to show what role except the religious and Sufi works which had a powerful popularity that period anyway, was played by the literature fiction works in the territory of Kazakhstan and how much they were demanded at that time which reflects a practical importance. On the basis of the conducted research, the author comes to light as in all this process the leading role was played by the founder of this publishing house – Munshi Naval Kishore, thanks to whom not only India, but also the whole world was able to get acquainted with the great Persian poets and their works which has made a huge contribution to the development and spiritual educa- tion of our country. Within the research, the theoretical method of research and analysis have been applied. Key words: Publishing house, Munshi Naval Kishore, overview, Indian, printing, publishing, Persian